How do graduate students approach college teaching? Influences of professional development, teaching assistantships, and Big Five personality traits - Che, Elizabeth S.; Brooks, Patricia J.; Schwartz, Anna M.; Saltzman, Ethlyn S.; Whiteman, Ronald C. (Frontiers in Education, 2023)
Graduate students engage in college teaching with varied attitudes and approaches. Through an online survey of graduate students teaching undergraduate courses (N = 109, 69.7% women, M age = 30 years, 59% psychology), we examined whether self-reported participation in professional development related to pedagogy, teaching assistantship (TA) experience, academic discipline (psychology vs. other), and Big Five personality traits were associated with variation in teaching practices. Participation in professional development correlated positively with years of undergraduate teaching experience and with the trait of openness. Hierarchical regressions indicated that professional development served to promote student-focused practices and discouraged lecturing, while TA experience (mostly restricted to psychology instructors) promoted lecturing and discouraged a student-focused approach. Regarding academic discipline, psychology instructors gave higher endorsements to an information transmission, teacher-focused approach to teaching, lectured more, and were less likely to provoke debate than instructors of other disciplines. Such differences may be attributed in part to larger enrollments of psychology courses. Regarding personality traits, both openness and agreeableness were associated with some student-focused practices, while conscientiousness was associated with an information transmission, teacher-focused approach and with practices aligned with backward course design. In light of previous evidence that personality traits are malleable, graduate training programs may want to cultivate traits like openness as a means of encouraging graduate students to reflect on their pedagogy and seek ways to improve their teaching through professional development. Relatedly, graduate programs should aim to support students’ participation in professional development related to pedagogy and, in doing so, communicate its value.